83.6k views
4 votes
7. 9-(5-7y) =13+4y

12. 5(3m+4) =3(4m+7)
14. 5(a+2)-3(3a-5) =1
17. 5(v+2) +3(v-5) =19

User Mugentoki
by
5.1k points

1 Answer

4 votes

Answer:

Explanation:

7) 9 - (5 - 7y) = 13 + 4y

9 - 5 + 7y = 13 + 4y

4 + 7y = 13 + 4y

7y = 13 + 4y - 4

7y - 4y = 13 - 4

3y = 9 {divide both side by 3}

y = 9/3

y= 3

12) 5(3m+4) = 3(4m+7)

5*3m + 5*4 = 3*4m + 3*7

15m +20 = 12m + 21

15m = 12m + 21 - 20

15m - 12m = 21 - 20

3m = 1

m = 1/3

14) 5(a+2) - 3(3a-5)=1

5*a + 5*2 + (-3)*3a -5 *(-3) = 1

5a + 10 - 9a + 15 = 1

5a - 9a + 10 + 15 = 1

-4a + 25 = 1

-4a = 1- 25

-4a = -24

a = -24/-4

a = 6

17) 5(v+2) + 3(v-5) = 19

5*v + 5*2 + 3*v - 5 * 3 = 19

5v + 10 + 3v - 15 =19

5v + 3v + 10 - 15 = 19

8v - 5 = 19

8v = 19 + 5

8v = 24

v= 24/8

v = 3

User Vinodh Kumar
by
5.8k points